A Perspective on Negotiation Research in Accounting and Auditing - J. Keith Murnighan; Max H. Bazerman (The Accounting Review, 1990)
[This paper proposes that interactions in accounting and auditing can be viewed as a large negotiation system. We define negotiations broadly to include any context in which two or more parties with differing preferences jointly make decisions that affect the welfare of both (all) parties. After a brief overview of negotiation research, the paper: (1) shows how recent research in accounting and auditing has implicitly addressed various aspects of negotiations; (2) comments on the Elias (1990) and Chalos and Haka (1990) studies which appear in this issue; (3) discusses departures from decision maker rationality which may seriously affect negotiations; and (4) uses three scenarios to highlight the importance of three negotiation issues (third party processes, the coordination of work groups, and social dilemmas) in accounting. We conclude by suggesting that a multifaceted research strategy, combining theory, description, and prescription, provides the greatest potential for progress in the study of accounting and auditing negotiations.]